Shaping tomorrow's auditors: the evolution of audit education - Ahmad @ Muhammad, Norizam; Mohd Noor, Azura; Mohamad Fadzillah, Fazni (Faculty of Accountancy, 2024)
The landscape of audit education stands at a pivotal crossroads, driven by rapid technological advancements and an increasing emphasis on ethical standards. As businesses worldwide grapple with the challenges of cybersecurity, data integrity, and compliance, the need for auditors who can navigate these issues with expertise and ethical clarity has never been more critical. This necessitates a significant transformation in audit education, acknowledging that the very nature of auditing is evolving in tandem with the digital age. Traditional auditing methods are evolving due to new technologies, and this necessitates a change in audit education. Thus, audit education must adapt to prepare the students not only to meet the current demands of the profession but also to anticipate future challenges, ensuring the integrity and reliability of financial reporting in an increasingly complex and interconnected global economy.